2019
DOI: 10.3390/en12152941
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Power Fluctuations Caused by the Unstable Flow in the Trifurcation of Multi-Turbine Diversion Systems with Common Penstock in Hydropower Units

Abstract: Stable operation is a challenge for hydropower stations with multi-turbine hydraulic coupled division systems with a common penstock. In this paper, the serious power fluctuations in a power station with such a division system are analyzed. The fluctuations occur in many conditions without any movement of the regulating system. The mathematical analysis illustrates that pressure fluctuation is responsible for power fluctuations. The computational fluid dynamics (CFD) method provided by ANSYS is used to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This junction, if not well designed, can lead to discharge unbalanced between the three penstocks. In [14], the authors considered a trifurcation with a spherical shape and they reported an amplitude of the discharge variation of approximately 30 m 3 s −1 in two of the three penstocks, leading to power fluctuations larger than 10 MW. Thanks to CFD simulations, the authors showed that the diameter of spherical trifurcation is responsible of the flow instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This junction, if not well designed, can lead to discharge unbalanced between the three penstocks. In [14], the authors considered a trifurcation with a spherical shape and they reported an amplitude of the discharge variation of approximately 30 m 3 s −1 in two of the three penstocks, leading to power fluctuations larger than 10 MW. Thanks to CFD simulations, the authors showed that the diameter of spherical trifurcation is responsible of the flow instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…But the model is still not refined enough. [23] focuses on controlling the power of multiple turbines with common pressure pipes by optimizing the flow stability.…”
Section: Introductionmentioning
confidence: 99%
“…Many causes can result in frequency oscillations, Energies 2021, 14,1933 2 of 19 such as the induction generator effect, turbine damping, the inertia ratio, proportionalintegral-derivative (PID) controller parameters, and the feed-forward controllers [11][12][13][14][15]. Hydraulic fluctuation is also a common cause of unstable regulation and operation in transient processes [16][17][18]. The proportion of hydropower in energy sources also affects the stability of a system [19].…”
Section: Introductionmentioning
confidence: 99%